Intergenerational teen pregnancy: a population based cohort study - Liu, Ning; Vigod, Simone; Farrugia, Michèle; Urquia, Marcelo; Ray, Joel (International Journal of Population Data Science, 2018)
Introduction Mothers can influence on a teen’s knowledge and attitude about sexual and reproductive health practices. Prior studies on intergenerational teen pregnancy between mother and daughter were largely limited to livebirths. Objectives and Approach To estimate the odds of intergenerational teenage pregnancy, and whether there is a coupling tendency between mother and daughter in how their teen pregnancies end, such as induced abortion (IA) vs. livebirth. A cohort study was conducted in Ontario, Canada among 15,097 mothers and their 16,177 daughters. The mother and her daughter were each assessed, between ages 15-19 years, for the number and nature of teenage pregnancy. The nature of teen pregnancy was categorized as i) no teen pregnancy, ii) ≥1 teen pregnancy, all exclusively ending with livebirth, and iii) ≥1 teen pregnancy, with at least one ending with IA. Results 13,036 daughters’ mothers had a teen pregnancy and 3,141 daughters’ mothers did not. Teen pregnancy occurred among 3,777(29.0%) and 513(16.2%) daughters, respectively. The adjusted odds ratio (aOR) of a daughter having a teen pregnancy was 1.42 (95% CI 1.25-1.61) if her mother had 1, 1.97 (95% CI 1.71-2.26) if her mother had 2, and 2.17 (95% CI 1.84-2.56) if her mother had ≥3 teen pregnancies, relative to none. If a mother had ≥1 teen pregnancy ending with IA, then her daughter had an aOR of 2.12 (95% CI 1.76-2.56) for having a teen pregnancy also ending with IA; whereas, if a mother had ≥1 teen pregnancy, all ending with livebirth, then her daughter had an aOR of 1.73 (95% CI 1.46-2.05) for that same outcome. Conclusion/Implications There is a strong intergenerational occurrence of teenage pregnancy between a mother and daughter, including a coupling tendency in how the pregnancy ends. Such evidence supports the use of family-centered interventions that engage parents to reduce unprotected sex and unintended pregnancies among teenagers.